Lactiplantibacillus Plantarum Postbiotics Suppress Salmonella Typhimurium Invasion and Modulate Innate Responses in Human Intestinal Epithelial Cells - Cobur, Hazal; Loker, Neriman; Dishan, Adalet; Vurmaz, Melike; Karatepe, Pinar; Hizlisoy, Harun; Al, Serhat (Springer, 2025)
Postbiotics derived from Lactiplantibacillus plantarum (LPP) exhibit promising potential as safe modulators of intestinal health. Here, the chemical, antimicrobial, and host-regulatory properties of LPP against Salmonella enterica serovar Typhimurium were investigated using a human intestinal epithelial (Caco-2) cell model. The LPP exhibited broad-spectrum antimicrobial activity against major foodborne pathogens, with minimal inhibitory concentrations ranging between 12.5 and 25 mg/mL. Treatment of Caco-2 cells with sub-MIC doses of LPP (6.25 mg/mL) significantly suppressed intracellular invasion of Salmonella (P < 0.05). Gene expression analysis revealed consistent downregulation of NF-kappa B gene expression following LPP presence with sublethal doses (P < 0.001), while no significant changes were detected in the expression levels of other key proinflammatory cytokines during the early phases (six and 12 h) of infection. A significant increase (P < 0.001) in apoptotic cell rates occurred at six h post-infection (PI), while no significant differences were observed at 12 h PI. The results revealed that LPP not only suppresses Salmonella invasion but also shows time-dependent modulation of inflammatory signaling and apoptotic responses in intestinal epithelial cells. These observed effects can be attributed to the bioactive compounds present in LPP, including organic acids, free amino acids, free fatty acids, polyphenols, and volatiles. The findings suggest that L. plantarum postbiotics can attenuate bacterial invasion and modulate innate immune response mechanisms without compromising host cell viability.
Keywords: Apoptosis; Caco-2 cell lines; Host-pathogen interactions; Innate response; Salmonella Typhimurium